Mentalità sostenibile e transizione ecologica: pilastri teorici e didattica per la scuola primaria e secondaria - Giuseppe De Simone; Maria Teresa Corrado (Studi sulla Formazione)
This article examines the interplay between education and ecological transition in the school context, exploring the skills necessary to promote sustainability in current and future generations. We delve into the meaning of sustainable mindset and analyze the intersection between ecological transition and circular economy, with a particular focus on the life-long learning approach and its psycho-pedagogical implications. From a bibliographic perspective, the research also concentrates on the importance of hands-on experience in primary and secondary schools, providing insights into how to effectively teach ecological transition and circularity. Ultimately, this contribution helps understand the crucial role education plays in promoting sustainable practices and preparing new generations to tackle complex environmental challenges.